THE INFLUENCE OF WORKLOAD, NON-PHYSICAL WORK ENVIRONMENT, COMPENSATION ON EMPLOYEE TURNOVER MEDIATED WITH ORGANIZATIONAL COMMITMENT - Andi Saputra; Sri Indarti; Yulia Efni (LPPM Press STIE Indragiri Rengat, 2021)
The research was conducted at PT Lutvindo Wijaya Perkasa Pekanbaru. The aim is to determine the direct effect of workload, non-physical work environment, compensation for employee turnover mediated by organizational commitment. This study took a sample of 160 customers. The variables used are workload, non-physical work environment, compensation for employee turnover mediated by organizational commitment. The data were analyzed using SEM (Structural Equation Modeling) analysis which was operated through the Smart PLS 3.2.8 . program.The results showed that there was a workload that had a significant effect on employee turnover at PT. Lutvindo Wijaya Non-physical work environment, compensation, organizational commitment and workload have a significant effect on employee turnover with organizational commitment as a mediating variable. Every increase in workload will increase employee turnover, and every decrease in workload will decrease employee turnover with organizational commitment as a mediating variable. The non-physical work environment has a significant effect on employee turnover with organizational commitment as a mediating variable. The better the non-physical work environment will reduce employee turnover, and the worse the non-physical work environment will increase employee turnover with organizational commitment as a mediating variable. Compensation has a significant effect on employee turnover with organizational commitment as a mediating variable. The greater the compensation received will reduce employee turnover, and the smaller the compensation received will increase employee turnover with organizational commitment as a mediating variable.